2019
DOI: 10.1159/000495978
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Iron Deficiency: Implications for Mothers and Infants

Abstract: Iron deficiency, with or without anemia, is common in pregnant women. In fact, nearly 30% of reproductive-age women are anemic worldwide, and anemia in pregnancy has an estimated global prevalence of 38%. Severe anemia can substantially increase the risk of maternal mortality, and can adversely affect fetal development. In this review, we examine the available data regarding epidemiology and consequences of iron deficiency in mothers and infants, current treatment strategies, and make recommendations for scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 36 publications
1
79
0
10
Order By: Relevance
“…A systematic review suggested that mild to moderate iron deficiency, even without established anemia, has adverse functional consequences 84 . The intergenerational transfer of poor iron status from mother to child has also been shown in several studies [85][86][87] . Iron deficiency amongst adolescent girls being future mothers increases the vulnerability of infants to iron deficiency and anemia as they are born with reduced or deficient pools of iron stores 88 .…”
Section: Ironmentioning
confidence: 64%
“…A systematic review suggested that mild to moderate iron deficiency, even without established anemia, has adverse functional consequences 84 . The intergenerational transfer of poor iron status from mother to child has also been shown in several studies [85][86][87] . Iron deficiency amongst adolescent girls being future mothers increases the vulnerability of infants to iron deficiency and anemia as they are born with reduced or deficient pools of iron stores 88 .…”
Section: Ironmentioning
confidence: 64%
“…IDA increases maternal morbidity and the risk of poor pregnancy outcomes, including intrauterine growth restriction, prematurity and low birth weight. 38 Compared to non-iron-deficient women, gravidas with depleted iron stores or IDWA at the start of pregnancy are more likely to develop pre-and postnatal ID and have a newborn with a lower birth weight. 39 Anaemia is a late manifestation of ID.…”
Section: Iron Deficiency In Pregnancymentioning
confidence: 99%
“…Вследствие этих нарушений метаболизма при ЖДА снижается физическая работоспособность, эффективность обучения, концентрация внимания [15,16]. Известно, что гипоксия и дефицит энергии аденозинтрифосфата вызывают нарушения внутриутробного развития плода, уменьшение веса новорожденных, нарушение когнитивных функций, а также задержку развития речи и двигательных навыков у детей младшего и подросткового возраста [17][18][19][20]. Экспериментально доказано, что нарушение созревания структур мозга при дефиците железа связано с недостаточной миелинизацией нервных волокон [17].…”
Section: Introductionunclassified
“…Таким образом, группу риска по развитию анемии составляют дети раннего возраста, беременные женщины, небеременные женщины репродуктивного возраста и пациенты с хроническими заболеваниями [1-3, 5- 7,19].…”
Section: Introductionunclassified